Effect of storage time and temperature on antioxidant components and properties of milled rice - Thanajiruschaya, Pimpaporn; Doksaku, Wathinee; Rattanachaisit, Phanee; Kongkiattikajorn, Jirasak (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this study was to determine the phenolic, flavonoid contents and antioxidant properties in the milled rice cv. Khaw Dawk Mali 105 during storage for 0-7 months at different temperature. The total phenolics content of non-stored rice was 17.02 mg/g and 7-month stored rice at 25°C was 6.07 ± 0.01 mg/g while storage for 7 months at 37°C, thephenolicscontents was7.29±0.35 mg/g. Thetotal flavonoidscontentsofnon-storedrice was13.26±0.01 mg/g and7 monthstoredriceat25°C was6.74±0.01 mg/g whilestoragefor7 monthsat37°C, the flavonoidcontent was6.45± 0.12 mg/g. The antioxidant property determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical expressed in the value of EC50 (DPPH) of non-stored rice was 0.27 mg/ml and 7- month stored rice at 25°C was 12.15 mg/ml while storage for 7 months at 37°C, the antioxidant property was 6.34 mg/ml. The antioxidant property determined by lipid peroxidation expressed in the value of EC50 (lipid peroxidation) of non-stored rice was 0.12 mg/ml and 7 month stored rice at 25°C was 1.18 mg/ml while storage for 7- months at 37°C, the antioxidant property was 1.10 mg/ml. The results showed that storage time at 25°C and 37°C caused decrease of extractable phenolic and flavonoid contents and antioxidant activities of the milled rice however 7- month stored milled rice at 37°C contained phenolic contents and antioxidant activities higher than stored milled rice at 25°C.